2020
DOI: 10.1111/jcmm.15098
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of hub genes for lymph node metastasis in patients with prostate cancer

Abstract: | INTRODUC TI ONProstate cancer (PCa) is the fifth principal cause of death and also the second most frequent cancer in males all over the world. 1 More than 15% of PCa patients harbour lymph node metastasis at radical prostatectomy. 2 Lymph node metastasis is a complicated process in which cancer cells leave the primary tumour site through the lymphatic system and then establish a secondary tumour site in lymph nodes. 3 These individuals have a higher risk of recurrence after primary treatment and usually suf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 39 publications
(45 reference statements)
1
17
0
Order By: Relevance
“…Meta-analysis on differential gene expression from primary tumors and metastasis are common for different cancer types. However, the analyses that stratify metastatic samples according to the secondary sites are rare with more interest shown in very recent years [ 29 , 30 , 31 , 32 , 33 ]. To the best of my knowledge, the work that is presented here is the first such study for prostate cancer and its most common metastasis sites.…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analysis on differential gene expression from primary tumors and metastasis are common for different cancer types. However, the analyses that stratify metastatic samples according to the secondary sites are rare with more interest shown in very recent years [ 29 , 30 , 31 , 32 , 33 ]. To the best of my knowledge, the work that is presented here is the first such study for prostate cancer and its most common metastasis sites.…”
Section: Discussionmentioning
confidence: 99%
“…WGCNA 14 is a popular systems biology algorithm that not only could effectively identify highly-connected and function-shared genes (in the same module) from thousands of genes in the microarray or sequencing data based on the correlation between genes due to their similar expression profile, but also could associate co-expression modules with clinical characteristics. Thus, WGCNA is a widely applied method to screen specific phenotype-associated genes in many cancers, including prostate cancer (castration-resistant-related, 19 Gleason score-related 20 and lymph node metastasis-related 21 ). Similar to these studies, we also used the WGCNA package in R (version 1.61; https://cran.r-project.org/web/packages/WGCNA/index.html ) 14 to identify modules highly correlated with bone metastasis of PCa in the GSE32269 dataset.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies reported that different gene expression profiles existed between metastatic PCa and localized PCa either in a single cohort (LaTulippe et al 2002;Varambally et al 2005;Chandran et al 2007;Taylor et al 2010) or in an integrated series (Liu et al 2018;Guo et al 2019;Xu et al 2020).…”
Section: Discussionmentioning
confidence: 99%